Perancangan Aplikasi Simulasi Investasi Berbasis GNU Octave GUI Untuk Edukasi Keuangan - Sembiring, Febe Gracia; Suleho, Febrina; Panjaitan, Clara Kresensia; Niska, Debi Yandra (STMIK Banjarbaru, 2025)
Advances in information technology open up great opportunities in developing simulation-based educational applications. This research designs and implements an investment simulation application based on the Graphical User Interface (GNU) Octave GUI to increase public financial literacy, especially in understanding the impact of inflation on the real value of investments. This application utilizes numerical computing programming and a graphical interface to present an interactive visualization of the comparison of nominal and real values of a long-term investment. The calculation process is based on a compound interest model and annual inflation correction. The methodology used follows the Waterfall model in software engineering, including the stages of analysis, design, implementation and system testing. Test results show that the application is able to produce accurate simulations and intuitive visualization, and is responsive to user input. By combining aspects of numerical computing, GUI programming, and data visualization, this application is a concrete example of the contribution of informatics in the development of open technology-based educational solutions.Keywords: GNU Octave; Graphical User Interface; Investment Simulation; Numerical Computing; Financial Literacy AbstrakKemajuan teknologi informatika membuka peluang besar dalam pengembangan aplikasi edukatif berbasis simulasi. Penelitian ini merancang dan mengimplementasikan aplikasi simulasi investasi berbasis Graphical User Interface (GNU) Octave GUI guna meningkatkan literasi keuangan masyarakat, khususnya dalam memahami dampak inflasi terhadap nilai riil investasi. Aplikasi ini memanfaatkan pemrograman komputasi numerik dan antarmuka grafis untuk menyajikan visualisasi interaktif perbandingan nilai nominal dan riil dari suatu investasi jangka panjang. Proses perhitungan didasarkan pada model bunga majemuk dan koreksi inflasi tahunan. Metodologi yang digunakan mengikuti model Waterfall dalam rekayasa perangkat lunak, mencakup tahapan analisis, desain, implementasi, dan pengujian sistem. Hasil pengujian menunjukkan bahwa aplikasi mampu menghasilkan simulasi yang akurat dan visualisasi yang intuitif, serta responsif terhadap input pengguna. Dengan menggabungkan aspek komputasi numerik, pemrograman GUI, dan visualisasi data, aplikasi ini menjadi contoh konkret kontribusi informatika dalam pengembangan solusi edukatif berbasis teknologi terbuka.